PENERAPAN KOMUNIKASI SANTUN PADA ANAK MADRASAH DINIYAH TAKMILIYAH (MDTA) AL-MUKARRAMAH KOTA PEKANBARU - Idawati, Idawati; Gazali, Novri; Aslinda, Cutra (Komunitas Manajemen Kompetitif, 2025)
Communication is a consequence of humans as social beings in carrying out their activities in the community. Communication aims to realize understanding between people involved in the process, on the other hand, if someone does not understand an event that is being communicated, it means that communication is considered not running, and it can be said that the relationship between people is not communicative. Applying polite communication to children is not as easy as applying polite language to adults, because a child does not understand the same level of language intelligence as adults. So a child will be able to understand polite communication, if it is often practiced by the people around him. This service aims to provide education on the application of polite communication to students of Madrasah Diniyah Takmiliyah (MDTA). In this service, an educational method is used by providing material on the application of polite communication to children, while providing a simulation of polite communication between MDTA children, the activity ran smoothly and orderly, all students were very enthusiastic about participating in this activity until it ended with a friendly activity, the activity lasted for approximately three hours. Attended by 40 MDTA students. The results of this activity show that students begin to understand polite communication in their daily activities, to being able to apply it in their families, schools, and peer environments.